Perubahan Pola Konsumsi Pakan Ternak dan Dampaknya terhadap Ketahanan Sosial-Ekonomi Peternak Tradisional - Hajar Hajar (Journal of Humanities, Social Sciences, and Education, 2025)
Changes in animal feed consumption patterns in the traditional livestock sector in Wakatobi Regency have become a central issue in maintaining the economic sustainability of livestock households. This study aims to analyze the shift in the types, sources, and forms of feed used by traditional livestock farmers and their implications for their social and economic well-being. The study employed a descriptive qualitative approach, with data collection techniques including in-depth interviews, field observations, and documentation in three livestock villages in Wakatobi. The results indicate a significant shift from the use of natural feed (such as wild grasses and local agricultural waste) to commercial feed, which is considered more efficient but results in increased production costs and reduced profit margins for livestock farmers. Beyond the economic impact, this shift in feed consumption patterns also impacts the social aspects of livestock farmers. Interactions between livestock farmers, once intense in the fields and pastures, have decreased due to increased workloads and dependence on external feed supplies. However, new social dynamics have emerged, such as the formation of joint venture groups and feed cooperatives, which have strengthened solidarity among livestock farmers facing common challenges. Therefore, this study recommends policy interventions in the form of training in local feed production based on regional potential, strengthening livestock cooperatives, and subsidizing feed ingredients as strategic efforts to strengthen the socio-economic resilience of traditional Wakatobi livestock farmers amidst the currents of agribusiness modernization.